Prevenção de lesões por pressão decorrentes do posicionamento cirúrgico em calcâneos: ensaio clínico randomizado autocontrolado - Eberhardt, Thaís Dresch (2020)
Pressure injury (PI) is a local damage to the underlying skin and/or soft tissues, usually over a bony prominence or related to the use of a medical device or other artifact. The study of PI prevention in surgical patients, in addition to experimental and intervention studies, is a gap in the knowledge produced in postgraduate programs in Brazil. The objective is to evaluate the efficacy of silicone multilayered foam (intervention) compared to transparent polyurethane film (control) in the prevention of PI resulting from surgical positioning in heels of hospitalized individuals undergoing elective surgeries. This is a self-controlled randomized clinical trial conducted in the Surgical Center of a hospital in the interior of Rio Grande do Sul/Brazil, from arch 2019 to February 2020. The study population consisted of patients undergoing elective surgical procedure. The patients who met the selection criteria constituted, simultaneously, a single group to receive the intervention and control, through paired analysis of the cutaneous sites (right and left heel). For data collection, the collectors made an initial visit to the patient preoperatively while still in the hospitalization unit; follow-up during the transoperative period; 24, 48 and 72 hours postoperatively. The primary outcome of this study is the difference in the relative risks – or risk ratio – of the PI resulting from surgical positioning in the intervention and control groups. Secondary outcomes were the temperature and moisture of the skin of the heels. Descriptive and inferential statistical analysis was performed with the help of the Statistical Package for the Social Sciences program. The guidelines and regulatory standards of researches involving human beings were respected, the research project was approved by the Ethics Committee under Certificate of Presentation for Ethical Assessment (CAAE) n. 77103617.6.0000.5346 and registered on the platform of the Brazilian Registry of Clinical Trials (ReBEC), approved under identifier RBR-5GKNG5. One hundred fifty-four patients (308 heels) were randomized and 135 patients (270 heels) were analyzed. Among the 270 skin sites analyzed, 100 developed PI (overall incidence of 36.7%). The incidence of PI was different among the intervention group (26.7%) and the control group (46.7%), with a relative risk of 0.57. A longer PI free time (survival) was identified in the intervention group (57.5 hours) compared to the control group (43.9 hours). The findings suggest that silicone multilayered foam is able to control the skin microclimate, while transparent polyurethane film demonstrates efficacy in temperature control and its action on skin moisture should be better investigated. Still, the back of the foot can be considered as a control region for the temperature of the heel skin. Regarding the risk factors related to the PI development, the surgical risk score of the American Society of Anesthesiologists (ASA) was identified. The thesis defended in this work, that silicone multilayered foam with silicone (intervention) is more effective than transparent polyurethane film (control) in the prevention of pressure injuries resulting from surgical positioning in heels of hospitalized individuals undergoing elective surgeries, was confirmed.